Construction of diverse peptide structural architectures via chemoselective peptide ligation. Issue 20 (23rd April 2021) - Cheung, Carina Hey Pui; Xu, Jianchao; Lee, Chi Lung; Zhang, Yanfeng; Wei, Ruohan; Bierer, Donald; Huang, Xuhui; Li, Xuechen
Abstract : Methods of introducing peptide salicylaldehyde esters and hydroxyl amine functionality into the peptide side chain have been developed. Diverse peptide structural motifs were constructed via ligation with native amide linkages at the ligation sites. Abstract : Herein, we report the development of a facile synthetic strategy for constructing diverse peptide structural architectures via chemoselective peptide ligation. The key advancement involved is to utilize the benzofuran moiety as the peptide salicylaldehyde ester surrogate, and Dap–Ser/Lys–Ser dipeptide as the hydroxyl amino functionality, which could be successfully introduced at the side chain of peptides enabling peptide ligation. With this method, the side chain-to-side chain cyclic peptide, branched/bridged peptides, tailed cyclic peptides and multi-cyclic peptides have been designed and successfully synthesized with native peptidic linkages at the ligation sites. This strategy has provided an alternative strategic opportunity for synthetic peptide development. It also serves as an inspiration for the structural design of PPI inhibitors with new modalities.